Secret diaries of miss miranda cheever ebook - Quinn, Julia (Bevelstoke, 2009)
2 March 1810 . . . Today, I fell in love. At the age of ten, Miranda Cheever showed no signs of Great Beauty. And even at ten, Miranda learned to accept the expectations society held for her—until the afternoon when Nigel Bevelstoke, the handsome and dashing Viscount Turner, solemnly kissed her hand and promised her that one day she would grow into herself, that one day she would be as beautiful as she already was smart. And even at ten, Miranda knew she would love him forever. But the years that followed were as cruel to Turner as they were kind to Miranda. She is as intriguing as the viscount boldly predicted on that memorable day—while he is a lonely, bitter man, crushed by a devastating loss. But Miranda has never forgotten the truth she set down on paper all those years earlier—and she will not allow the love that is her destiny to slip lightly through her fingers . . .